ANTHROPOLOGICAL-MANAGERIAL INTEGRATION: EXPLORING COLLECTIVE ORGANIZATIONAL VALUES WITHIN THE FRAMEWORK OF STRATEGIC ADAPTATION - Achmad Luthfi Chamidi; Ashlihah Ashlihah; Ahmad Hanif Fajrin; Dede Nurohman; Prim Masrokan Mutohar (Procuratio : Jurnal Ilmiah Manajemen, 2026)
This study aims to explore the synergistic relationship between the anthropological and managerial dimensions of organizational culture as an instrument of strategic adaptation. Amid global disruption, organizations often fail to transform not because of poor strategic planning, but because of neglecting their anthropological "cultural roots." Using a literature review method by analyzing various models of organizational culture, this article builds an argument that organizational culture is not merely a supporting factor, but rather the foundation or "operating system" for strategic success. The results of the study indicate that effective integration requires synchronization between the collective mental programs of organizational members and systematic managerial interventions. In conclusion, an organization's ability to adapt depends heavily on the strength of dynamic and innovative collective values as a compass in facing market changes. Penelitian ini bertujuan untuk mengeksplorasi hubungan sinergis antara dimensi antropologis dan manajerial dalam budaya organisasi sebagai instrumen adaptasi strategi. Di tengah disrupsi global, organisasi seringkali gagal melakukan transformasi bukan karena buruknya rencana strategis, melainkan karena pengabaian terhadap "akar budaya" yang bersifat antropologis. Menggunakan metode literature review dengan menganalisis berbagai model budaya organisasi, artikel ini membangun argumen bahwa budaya organisasi bukanlah sekadar faktor pendukung, melainkan landasan atau "sistem operasi" bagi keberhasilan strategi. Hasil kajian menunjukkan bahwa integrasi yang efektif memerlukan sinkronisasi antara program mental kolektif anggota organisasi dengan intervensi manajerial yang sistematis. Kesimpulannya, kemampuan organisasi untuk beradaptasi sangat bergantung pada kekuatan nilai-nilai kolektif yang dinamis dan inovatif sebagai kompas dalam menghadapi perubahan pasar.